The vices of nullity and their impact on the management of the procedures administrative disciplinary in 2019 - Torres Morón, Eliana Sthefanie (2021)
This article is oriented to explain and publicize the incidence the vices of nullity in the management of the procedures administrative disciplinary developed by public entities in 2019, as part of the exercise of their power disciplinary in order to guarantee the proper functioning of the Public Administration. This article analyzes responsibility administrative disciplinary that reaches to servants public in the exercise of their functions when they incur in acts that are contrary to the legal system, what causes them to be judged through an procedure administrative disciplinary in order to impose a penalty. However, in the development of said procedure administrative disciplinary, it is frequent that vices occur that lead to the invalidity of the referred procedures. In this sense, the analysis of this article was carried out on the basis of 50 servers from different entities public, who were surveyed, having come to determine as a result some factors that give rise to the production of vices nullity, as well as the consequences harmful that these vices generate for the proper management of procedures disciplinary administrative.